2004
DOI: 10.1148/radiol.2331031803
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced Voiding US for Grading of Reflux in Adult Patients Prior to Antireflux Ureteral Implantation

Abstract: A high rate of agreement was seen between voiding US and VCUG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Contrast-enhanced voiding urosonography has been used for vesicoureteral reflux in renal transplant recipients with recurrent urinary tract infections [65 -67], both in adults and children. In 23 adult renal transplant recipients, ceVUS was compared with radionuclide cystography [65], in 37 adult patients ceVUS was compared with conventional voiding cystourethrography [66] and in 27 patients (8 children or adolescents, 19 adults) cycling ceVUS (i. e., obtained by filling the bladder and having the patient void around the urinary bladder catheter two times) was compared with ceVUS in the first cycle [67]. Results indicated that ceVUS was highly effective in detecting vesicoureteral reflux in adult renal transplant recipients.…”
Section: Diagnosis Of Vesicoureteral Refluxmentioning
confidence: 99%
“…Contrast-enhanced voiding urosonography has been used for vesicoureteral reflux in renal transplant recipients with recurrent urinary tract infections [65 -67], both in adults and children. In 23 adult renal transplant recipients, ceVUS was compared with radionuclide cystography [65], in 37 adult patients ceVUS was compared with conventional voiding cystourethrography [66] and in 27 patients (8 children or adolescents, 19 adults) cycling ceVUS (i. e., obtained by filling the bladder and having the patient void around the urinary bladder catheter two times) was compared with ceVUS in the first cycle [67]. Results indicated that ceVUS was highly effective in detecting vesicoureteral reflux in adult renal transplant recipients.…”
Section: Diagnosis Of Vesicoureteral Refluxmentioning
confidence: 99%
“…1 Recently, the value of intracavitary administration of microbubble contrast agent in diagnosis of vesicoureteric reflux has been reported. 2 Robert et al 3 have used CEUS to display a porcine biliary tree by injecting micro-bubbles into the bile ducts. We report a case of biliary leakage in the common bile duct (CBD) following a T-tube removal, which was diagnosed with CEUS after injection of micro-bubble contrast medium into the bile ducts through the percutaneous transhepatic biliary drainage catheter.…”
mentioning
confidence: 99%
“…A few reports discussing the application of contrast-enhanced sonography for visualizing extravascular space have been described. [21][22][23] Although this report is limited to a single case, it is hoped that the use of contrast-enhanced sonography will enable a prompt diagnosis of this entity. Sonography has been recognized as a safe, relatively inexpensive and highly effective diagnostic procedure.…”
Section: Discussionmentioning
confidence: 99%